Legal Adaptation in the Age of Digital Creativity: A Global Review - Widaningsih (Sinergi International Journal of Law, 2024)
The rapid digitalization of creative industries has intensified the urgency to reassess copyright protection in the face of emerging technologies such as artificial intelligence, blockchain, and Digital Rights Management (DRM). This study aimed to explore the legal, technological, and policy challenges of digital copyright through a comprehensive narrative review of international academic literature and policy documents. Using thematic analysis, this study synthesized research findings and regulatory responses related to digital authorship, streaming piracy, fair use in digital education, and technological enforcement tools. Results show a growing disparity in copyright protection effectiveness between developed and developing countries due to differences in infrastructure, legal systems, and policymaking speed. The increasing prevalence of AI-generated content challenges traditional notions of authorship and moral rights. Blockchain is found to offer significant potential for transparent copyright verification, yet legal recognition remains inconsistent. DRM systems, while technically protective, often limit legitimate access and educational use. The findings underscore the necessity of harmonized international regulations, enhanced digital literacy, and adaptive national policies that consider cultural and infrastructural contexts. Recommendations include redefining authorship in the AI era, integrating fair use provisions into legal frameworks, and supporting controlled digital lending in educational institutions. This review highlights that the sustainable future of copyright in the digital era lies in legal flexibility, technological innovation, and inclusive policy development. Further interdisciplinary research is crucial to bridge the gap between technological advancement and equitable legal protection.